2019
DOI: 10.1002/ijc.32575
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to ambient air pollution and the incidence of lung cancer and breast cancer in the Ontario Population Health and Environment Cohort

Abstract: Lung and female breast cancers are highly prevalent worldwide. Although the association between exposure to ambient fine particulate matter (PM2.5) and lung cancer has been recognized, there is less evidence for associations with other common air pollutants such as nitrogen dioxide (NO2) and ozone (O3). Even less is known about potential associations between these pollutants and breast cancer. We conducted a population‐based cohort study to investigate the associations of chronic exposure to PM2.5, NO2, O3 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
81
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 61 publications
(170 reference statements)
4
81
1
2
Order By: Relevance
“…A growing body of evidence indicates that lung cancer incidence is associated with exposure to PM 2:5 (IARC 2013;Bai et al 2020;Zhang et al 2020). The present study supports this evidence, with a statistically significant IRR of 1.19 (95% CI: 1.09, 1.30), even after conservatively adjusting for multiple comparisons (p = 0:01).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A growing body of evidence indicates that lung cancer incidence is associated with exposure to PM 2:5 (IARC 2013;Bai et al 2020;Zhang et al 2020). The present study supports this evidence, with a statistically significant IRR of 1.19 (95% CI: 1.09, 1.30), even after conservatively adjusting for multiple comparisons (p = 0:01).…”
Section: Discussionsupporting
confidence: 84%
“…Much of the epidemiological evidence to support this association, however, is based on prospective cohort studies that examined lung cancer mortality, not lung cancer incidence. Although several recent studies have used incidence data to estimate the association between PM 2:5 and lung cancer (IARC 2013;Bai et al 2020;Zhang et al 2020), further research is needed to confirm the association and examine the sensitivity of the results to modeling choices and exposure windows.…”
Section: Introductionmentioning
confidence: 99%
“…14 Bai et al showed the positive associations of lung cancer incidence with PM2.5 and NO2 in the Ontario Population Health and Environment Cohort. 15 This reminds us that the pathogenesis of young lung cancers and old ones may be different due to changes in external factors.…”
Section: Discussionmentioning
confidence: 94%
“…To note that both air pollution and water pollution indices are high (76.91 and 78.08, respectively) [19]. Although, the impact of pollution on the development of breast cancer remains debatable; certain studies affirm a completely negative association linking air pollution to breast cancer [20]. Notably, the psychological and emotional impact of breast cancer diagnosis seen among young patients is stronger and more detrimental when compared to the impact seen in older patients [21].…”
Section: Discussionmentioning
confidence: 99%